Psychometric Properties of the Effort-Reward Imbalance Questionnaire for Teachers (Teacher ERIQ) - Ren, Chuang; Li, Xiying; Yao, Xuemei; Pi, Zhongling; Qi, Senqing (Frontiers in Psychology, 2019)
The Effort-Reward Imbalance (ERI) Model is a theoretical model of a psychosocial work environment with adverse effects on health and well-being that focuses on a mismatch between high efforts spent and low rewards received at work. This study aimed to develop and psychometrically test an Effort-Reward Imbalance Questionnaire for Teachers (Teacher ERIQ) based on the ERI model. The structure validity, reliability and criterion validity of the new questionnaire’s scores were evaluated in a sample of 475 Chinese teachers. The results of Exploratory factor analysis and Confirmatory factor analysis showed that a structure of four factors of effort (workload, emotional demands, student-related issues, social responsibility) and two factors of reward (emotional reward and material reward) in accordance with the ERI model had significant factor loadings and acceptable model fit. The Cronbach’s Alpha coefficients of all dimensions’ scores showed that the scores of questionnaire had good reliability. Criterion validity was indicated by the significant correlation coefficients of scores of most dimensions with teachers’ self-reported job burnout and non-reciprocal social relations, as well as the ANOVA results that the differences of scores of the two criterion scales in different ERI ratio levels was significant. The results also showed that teacher’s ERI level varied with demographic variables such as age, gender and school type. The Teacher ERIQ is a valid and reliable new measurement for assessing teachers’ psychosocial work characteristic. It can be an important tool to provide new explanations of stress-related health risks among teachers and to guide the development of preventive measurements.